Good for business, good without reservation? Veblen's critique of business enterprise and pecuniary culture. (August 2015) - Smart, Barry
Thorstein Veblen's work undoubtedly has a place within the field of institutional economics but he has been a relatively marginal figure within the discipline of sociology. If Veblen is discussed at all within contemporary sociology, it is almost without exception in relation to his first major work The Theory of the Leisure Class and his principal contribution to our understanding of modern social life is considered to flow from observations on consumer conduct and associated practices and predispositions. While The Theory of the Leisure Class is a significant work, it by no means exhausts the contemporary relevance of Veblen's oeuvre. It is argued in this article that in a series of subsequent interconnected studies which embed economic matters in their social and political context, Veblen proceeded to develop a powerful critical analysis of business enterprise and pecuniary culture, one that bears comparison with aspects of Karl Marx's work. Veblen's early twentieth-century critical political economy, his references to social and economic dilemmas and tensions as well as his identification of the potential scope for change or 'reconstruction' arising from substantial conflicts of interest between 'the established order of business' preoccupied with maximising profit and 'the underlying population who work for a living' are of considerable contemporary significance, as is his recognition that what is good for business is not good without reservation, not necessarily good for the community or 'the common man'.